If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(b + -2) = 7b + -22 Reorder the terms: 5(-2 + b) = 7b + -22 (-2 * 5 + b * 5) = 7b + -22 (-10 + 5b) = 7b + -22 Reorder the terms: -10 + 5b = -22 + 7b Solving -10 + 5b = -22 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. -10 + 5b + -7b = -22 + 7b + -7b Combine like terms: 5b + -7b = -2b -10 + -2b = -22 + 7b + -7b Combine like terms: 7b + -7b = 0 -10 + -2b = -22 + 0 -10 + -2b = -22 Add '10' to each side of the equation. -10 + 10 + -2b = -22 + 10 Combine like terms: -10 + 10 = 0 0 + -2b = -22 + 10 -2b = -22 + 10 Combine like terms: -22 + 10 = -12 -2b = -12 Divide each side by '-2'. b = 6 Simplifying b = 6
| -8x+y=3 | | 5x+2*3x-1= | | -302=-5(4+8r)-2 | | 2n-2+2n-4=5 | | 5v+23=-2 | | 4x-8=2ax-2b | | 7/3(-16)-12= | | 5.5(-3*7.5)= | | x-0.13x= | | 3(7)+7y=84 | | -8(x+9)+8=-64 | | Y+8+y=5+2(y-6) | | 14x^3+35x-7x=0 | | 2u+8=-18 | | 2/3(-16)+4= | | 8x+11=14x-1 | | -15-2y=18 | | -12=2+2v+5v | | 9t+11=11 | | -40=8+-6s | | 3x+7(0)=84 | | 2(2x-5)=3(x-5)+4(2x-3) | | -24-2y=18 | | 3(0)+7y=84 | | 3(-13+1)=2(-13-5) | | 3.9=n+8.3-2.9 | | 5y+o=51 | | 4d-6=9d+2 | | x^2+x+-20=0 | | 2s+18=0 | | 8x+24x^3= | | -4.3x+3.2x=-3.52 |